Model pengembangan pengelolaan hasil tangkap ikan masyarakat pesisir kabupaten Pasuruan melalui pendekatan linear programming dan business model canvas dalam industri 4.0 - M. Imron Masud; Abdul Wahid (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Pasuruan Regency is one area that has the potential to manage fishing products because this area has a coastal area whose people work as fishermen. Based on the potential of natural resources possessed, the level of income and welfare of coastal communities can be better than other village areas. However, the level of income and welfare of coastal communities is still lacking, one of which is less than optimal in processing fishing products. The purpose of this study is to optimize the processing of coastal fishing products and formulate business strategies through the Linear Programming and Business Model Canvas methods. The final result obtained is a profit value of Rp. 84,642.33 per person, while the Model of the Development of Fishing Management of coastal communities in facing the industrial era 4.0 in order to create added value through the use of online media.